Percepções de professores e coordenadores pedagógicos acerca da formação continuada, do ensino de ciências e da diversidade - Dias, Rodolfo Faita (Universidade Federal de São Carlos, 2022)
According to the literature, the process of continuing education about the theme of diversity has not been yet explored in all its potential, especially regarding to the role of pedagogical coordinators and Natural Science teachers responsible for Cycle II of Elementary School. Observing the importance of this type of training in that perspective, this study aims to identify and understand the perceptions of these school agents about continuing education for the context of diversity in municipal schools in the city of Araras, São Paulo estate. In this sense, this qualitative research sought to encompass documentary research to understand and to map the teaching network, as well as to guide the selection of schools and subjects. In addition, a more specific data collection was carried out with semi-structured interviews and a complement with a focal group perspective involving science teachers and pedagogical coordinators, in order to reach the main goals outlined in order to analyze the perceptions and possible actions of pedagogical coordinators and natural science teachers and about the process of continuing education for diversity in the years of Cycle II of Elementary Education in the schools around Araras city. Ten interviews and a videoconference were carried out using the focal group, in which three Pedagogical Coordinator Professors participated. The results indicate that school agents present conceptions and they are concerned about the working in diversity, evidencing, in their speech, the need for formative moments that contemplate these issues and they have dialogical characteristics, enabling the exchange of experiences and considering the identities of the subjects that take the teaching and learning process together.
Perceptions of teachers and pedagogical coordinators about continuing education, science teaching and diversity
Keywords: Coordenação pedagógica; Educação básica; Formação pós-inicial; Pedagogical coordination; Basic education; Post-initial training; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM